The impact of EU and Non-EU immigration on British wages - Stephen Nickell; Jumana Saleheen (IZA Journal of Development and Migration, 2017)
There is a consensus among academics that immigration has little or no effect on native British wages, but these studies have not refined their analysis by occupations. Our contribution is to extend the literature to incorporate occupations. Doing so, we find that immigration has a small negative impact on average British wages, with a somewhat larger impact within the semi/unskilled service occupations. This paper also explores if there is any differential impact between EU and non-EU immigration on wages. We find there to be none. These findings are likely to be useful for shaping future immigration policy in Britain.
Keywords: J6; 330; Immigration; Occupation; Wages